Pengembangan Kegiatan Kurikuler Sebagai Strategi Madrasah dalam Pencegahan dan Penanganan Bullying - Raikhan (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
Madrasas as Islamic educational institutions must be free from bullying, after the issuance ofPermendikbudristek number 46 of 2023 which regulates the prevention and handling of violence within educational unitsin Indonesia. This research wants to know the efforts of madrasas in handling and preventing axes of violence or bullyingin the madrasa environment. The research was carried out using a qualitative approach with a case study type of research.The results of this research show that madrasah strategies in preventing and handling bullying are implemented throughthree curricular activities, namely Intracurricular, Co-curricular and Extracurricular activities. Prevention and handlingactivities in extracurricular activities include learning discipline, discipline in entering class on time, discipline in dressingneatly, discipline in completing school assignments, discipline in listening when the teacher explains, discipline in lining upneatly, discipline in obeying madrasa rules. Co-curricular activities include ceremonies, roll calls, and Dhuha and Dhuhurcongregations, while extra-curricular activities include scouts, various sports teams, and the arts. The prevention valuesthat are instilled are obedience, conformity and order. Barriers to prevention and treatment are uncertain start times foractivities, lateness, use of students' personal books (BPS), lateness, activeness, students' lack of interest. The solution isstudents' personal books, working together with the boarding school administrators, making a picket teacher schedule,holding outreach by the madrasa head to all teachers, and building competent activities